A Red Skin in the Setting of Chickenpox: A Rare Report of Eosin Toxicity - Bahareh Abtahi‐Naeini; Fereshte Rastegarnasab; Zahra Pourmoghaddas; Shadi Asad Samani; Saeed Yousefian; Zahra‐Sadat Mirian (Clinical Case Reports)
ABSTRACT Eosin Yellowish (Eosin‐Y) is an effective treatment option for a range of dermatological conditions. It is crucial to carefully identify patients presenting systemic adverse reactions related to topical aqueous Eosin‐Y overuse and to monitor them closely during short‐term use to prevent severe complications.